HIGHER EDUCATION IN THE DIGITAL AGE: ASSESSING THE ROLE OF MOBILE APPS IN CAMPUS LIFE - Hapini Awang; Nur Suhaili Mansor; Ramlan Mustapha; Nurul Izzah Mohamad Ghozali (Journal of Islamic, Social, Economics and Development, 2023)
In today's digital era, mobile devices have become ubiquitous in people's lives. This research investigates the significance of mobile applications in assisting higher education students. Our approach involved the administration of a questionnaire to assess the types of mobile applications used by students and the frequency of their usage. Our findings indicate that students predominantly utilize mobile applications for educational, communication, and entertainment purposes. Notably, higher education students frequently engage with mobile applications. This study underscores the importance of mobile technology as an educational tool, particularly in facilitating efficient access to a wealth of information for learning purposes.